Modification of Paving Block Molding Machine with the Addition of an Automatic Control System Based on a Programmable Logic Controller (PLC) - Safitri, Laksita Aji; Darmawan, Andri; Sampurno, Bambang; Mashuri, Mashuri (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
Company X is a paving block molding machine fabrication company in Surabaya. However, the machine still has some shortcomings because it is still conventional or manually operated. Some of these shortcomings, such as being still prone to human error and being less consistent when operating, can affect the results of the amount of production. From this phenomenon, automation is very important in the industrial world. Therefore, by referring to previous phenomenon, through this research, an automatic control system is made on paving block molding machine using PLC. The results showed that PLC succeeded in developing a system that works automatically on the machine. Then, the ladder diagram used several instructions, including interlock, timer, counter, and set reset according to how the machine works. Then, the PLC-based automatic control system has a shorter cycle time than the original manual machine. Cycle time has decreased by 15.4%. From this decrease in cycle time, if simulated related to production capacity, an automatic control system can increase production per hour by 300 pcs more than the manually operated machine.